2022
DOI: 10.1002/glia.24174
|View full text |Cite
|
Sign up to set email alerts
|

The two pore potassium channel THIK‐1 regulates NLRP3 inflammasome activation

Abstract: The NLRP3 (NLR family, pyrin domain containing 3) inflammasome is a multi‐protein complex responsible for the activation of caspase‐1 and the subsequent cleavage and activation of the potent proinflammatory cytokines IL‐1β and IL‐18, and pyroptotic cell death. NLRP3 is implicated as a driver of inflammation in a range of disorders including neurodegenerative diseases, type 2 diabetes, and atherosclerosis. A commonly reported mechanism contributing to NLRP3 inflammasome activation is potassium ion (K+) efflux a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
25
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 34 publications
(26 citation statements)
references
References 68 publications
0
25
0
1
Order By: Relevance
“…P2X7, a kind of P2 receptors can be activated by ATP aggregation, which is required for ATP aggregation-induced activation of NLRP3 [ 25 ]. In recent years it has been found that P2X7 may partially regulate K + currents through the two-pore domain K + channels, such as Pore Domain Halothane-Inhibited Potassium Channel 1 (THIK-1) and Two-pore domain Weak Inwardly rectifying K + channel 2 (TWIK-2) [ 26 ] (Fig. 3 ).…”
Section: Cellular Events Related To Nlrp3 Activationmentioning
confidence: 99%
See 1 more Smart Citation
“…P2X7, a kind of P2 receptors can be activated by ATP aggregation, which is required for ATP aggregation-induced activation of NLRP3 [ 25 ]. In recent years it has been found that P2X7 may partially regulate K + currents through the two-pore domain K + channels, such as Pore Domain Halothane-Inhibited Potassium Channel 1 (THIK-1) and Two-pore domain Weak Inwardly rectifying K + channel 2 (TWIK-2) [ 26 ] (Fig. 3 ).…”
Section: Cellular Events Related To Nlrp3 Activationmentioning
confidence: 99%
“…Researchers found that THIK-1 is required for NLRP3-dependent Caspase-1 activation and IL-1β release in response to ATP. By blocking THIK-1, it inhibits the release of Pro-inflammatory cytokine il-1β from the activated microglia, which suggests that THIK-1 may be a therapeutic target for Nervous system inflammation diseases [ 26 , 60 ].…”
Section: Inflammasomes Ion Channels and Diseasesmentioning
confidence: 99%
“…The THIK-1 (two pore domain halothane-inhibited K + ) channel is a member of K2P channel family, whose mRNA was shown to express in neuronal cells [8,9]. The functional THIK-1 channel is expressed in neuronal cells [10][11][12][13] and shown in microglia [14][15][16]. THIK-1 is reported to regulate the microglial raminification and surveillance, and to contribute to the synapse development and the NLRP3 inflammasome activation [14][15][16].…”
Section: Introductionmentioning
confidence: 99%
“…The functional THIK-1 channel is expressed in neuronal cells [10][11][12][13] and shown in microglia [14][15][16]. THIK-1 is reported to regulate the microglial raminification and surveillance, and to contribute to the synapse development and the NLRP3 inflammasome activation [14][15][16]. The THIK-1 channel was also suggested to contribute to the apoptosis through irreversibly increasing its K + conductance by caspase-8 dependent truncation of the C-tail [17].…”
Section: Introductionmentioning
confidence: 99%
“…The role of K + efflux in canonical NLRP3 activation, in response to many stimuli, is well documented, and several ion channels have been suggested to mediate this K + current in microglia. One such channel is encoded by the KCNK13 (K 2P 13.1) gene, which translates to a two-pore forming domain K + channel, also known as THIK-1. , We previously showed that, when N uclear E nriched T ranscript S ort SEQ uencing (NETSseq) is used, KCNK13 is specifically expressed in human microglia and transcript levels increase in microglial nuclei isolated from post-mortem brain tissue from patients with Alzheimer’s disease compared to nonaffected control donors . This observation has been confirmed by a recent study demonstrating a significant increase in RNA and reduction in DNA methylation of KCNK13 in brain tissue from patients with Alzheimer’s and Parkinson’s disease .…”
mentioning
confidence: 99%